Pendidikan Karakter Sebagai Pondasi Pembangunan Bangsa : Peran Aktif Masyarakat Dan Implementasinya - Chusnur Rahmi; Musran; Arusman; Ema Sulastri (JKA, 2024)
Character education is an important issue in an effort to rebuild the character of the Indonesian nation that is experiencing moral degradation. This paper aims to examine the active role of the community in the implementation of character education as the foundation of nation development. The method used is a literature study by reviewing various reference sources related to character education. The results showed that the community has an important role in the implementation of character education, not only through the role of government and schools. The community can play an active role through habituation in daily life, community activities, and non-formal education. It is expected that with the active role of the community, a strong national character can be formed as the foundation of Indonesia's development.